Peran KUB Maju Bersama pada Implementasi Teknologi Tepat Guna Pencacah Sampah Organik dalam Produksi Kompos - M Imam Arifandy; Ningsih Amira; Dina Sefriana; Muhammad Abdul Azis; Muhammad Fikri; Gilang Saputra Efendi; Ranti Yurda Oktia (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This research discusses the application of appropriate technology (AT) in the form of an organic waste shredder machine at the Maju Bersama Joint Business Group (KUB) in Nagari Kamang Tangah Anam Suku, West Sumatra. The research used a descriptive qualitative method with in-depth interviews. This research analyzes the role of organizations in implementing TTG thru four main aspects: inter-organizational task roles, resource task roles, service task roles, and extra-organizational roles. The research results show that inter-organizational task roles are reflected thru coordination and partnerships between TTG institutions, village governments, relevant agencies, and financial institutions that support program planning and implementation. The role of resource tasks is evident in KUB's ability to manage funding, human resources, and organic waste raw materials in an integrated manner to support the sustainability of activities. The role of service tasks is realized thru direct mentoring, technical guidance, and training provided to KUB members, thereby enhancing community skills and independence in operating technology. Meanwhile, the extra-organizational role is evident in efforts to build networks with external parties, the use of social media as a means of disseminating innovation, and the involvement of universities in developing technology based on local needs. Overall, these four roles are interconnected and contribute to improving the effectiveness of appropriate technology implementation and supporting community empowerment based on organic waste management.